2016
DOI: 10.1007/s11356-016-6849-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating levels and health risk of heavy metals in exposed workers from surgical instrument manufacturing industries of Sialkot, Pakistan

Abstract: The study aimed to monitor heavy metal (chromium, Cr; cadmium, Cd; nickel, Ni; copper, Cu; lead, Pb; iron, Fe; manganese, Mn; and zinc, Zn) footprints in biological matrices (urine, whole blood, saliva, and hair), as well as in indoor industrial dust samples, and their toxic effects on oxidative stress and health risks in exposed workers. Overall, blood, urine, and saliva samples exhibited significantly higher concentrations of toxic metals in exposed workers (Cr; blood 16.30 μg/L, urine 58.15 μg/L, saliva 5.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 50 publications
4
12
0
Order By: Relevance
“…A positive correlation was also observed between Ni and Cr (r ¼ 0.57) concentrations measured in different bio-matrices, which implied the recent occupational exposure. Both of these metals showed the synergistic relationship in the surgical industries as per our current and previous findings (Junaid et al, 2016a). Moreover, these two metals were also significantly correlated (p < 0.05) in the dust samples and this was further confirmed by the augmented levels of Cr (34.28e299.75 mg/kg) and Ni (13.29e164.59 mg/kg) measured in the indoor industrial dust samples compared to the other metals ( Fig.…”
Section: Correlation and Regression Analysis Of Heavy Metalssupporting
confidence: 87%
See 4 more Smart Citations
“…A positive correlation was also observed between Ni and Cr (r ¼ 0.57) concentrations measured in different bio-matrices, which implied the recent occupational exposure. Both of these metals showed the synergistic relationship in the surgical industries as per our current and previous findings (Junaid et al, 2016a). Moreover, these two metals were also significantly correlated (p < 0.05) in the dust samples and this was further confirmed by the augmented levels of Cr (34.28e299.75 mg/kg) and Ni (13.29e164.59 mg/kg) measured in the indoor industrial dust samples compared to the other metals ( Fig.…”
Section: Correlation and Regression Analysis Of Heavy Metalssupporting
confidence: 87%
“…For Saliva samples, the surgical industries revealed higher levels of Ni, Pb, Mn, and Zn, while in the leather industries; Cr, Cd, Cu, and Fe levels were reported with elevated concentrations. Generally, the metal levels in the saliva samples were lower compared to other bio-matrices, previous studies also reported similar findings (Gil et al, 2011;Junaid et al, 2016a).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations